2019
DOI: 10.1186/s10195-019-0524-4
|View full text |Cite
|
Sign up to set email alerts
|

Should evoked potential monitoring be used in degenerative cervical spine surgery? A systematic review

Abstract: Background Intraoperative somatosensory evoked potential (SSEP) and transcranial motor evoked potential (tcMEP) monitoring are frequently used in spinal as well as spinal cord surgery for so-called intraoperative neuromonitoring (IONM), while the combination of these techniques is known as concomitant multimodal intraoperative monitoring (MIOM). The aim of this review is to collect available evidence concerning use of IONM and MIOM in cervical decompression surgery in the degenerative setting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…A recent systematic review reported that intraoperative monitoring may be a helpful tool in these surgical procedures given its high sensitivity and specificity for intraoperative neural damage detection. However, at this time evidence is limited, with no criteria for indications for its use [60]. An earlier systematic review made similar conclusions, noting that MEP/SEP monitoring may provide a sensitive tool for detecting neurologic injury during anterior approaches, intraoperative changes are not specific, and its recognition has not been found to prevent neurologic injury or result in improved outcome [61].…”
Section: Surgical Managementmentioning
confidence: 99%
“…A recent systematic review reported that intraoperative monitoring may be a helpful tool in these surgical procedures given its high sensitivity and specificity for intraoperative neural damage detection. However, at this time evidence is limited, with no criteria for indications for its use [60]. An earlier systematic review made similar conclusions, noting that MEP/SEP monitoring may provide a sensitive tool for detecting neurologic injury during anterior approaches, intraoperative changes are not specific, and its recognition has not been found to prevent neurologic injury or result in improved outcome [61].…”
Section: Surgical Managementmentioning
confidence: 99%
“…Numerous papers investigated novel technology to detect damage during orthopaedic surgery. This includes spectroscopy 15 , electrical conductivity devices 61,62 , electromyography 63 , stimulus-evoked potential 64 , bioimpedance drills 65 , and acoustic emission-signal analysis 66 .…”
Section: Resultsmentioning
confidence: 99%
“…Two of these were systematic reviews that investigated proximal femoral fractures 6 and total hip arthroplasty 12 , with the majority being retrospective studies and 1 questionnaire sent to vascular surgeons 22 . In addition, there were multiple case reports of arterial, nervous, and ureteric injury due to screw placement and drill bit use [24][25][26][27][28][29] 15 , electrical conductivity devices 61,62 , electromyography 63 , stimulus-evoked potential 64 , bioimpedance drills 65 , and acoustic emission-signal analysis 66 .…”
Section: Prevalence Of Iatrogenic Injury Using Power Toolsmentioning
confidence: 99%
“…Although IONM was developed partly in hope of reducing intraoperative neurological events during spinal surgery, its utility and value continue to be debated in the literature due to its associated cost, set-up time, and reported sensitivity and specificity. 14,20,21,23 Part of the issue with IONM is that intraoperative neurological events are relatively rare, thus the number needed to treat to potentially save a single event may be quite high. Moreover, among those rare neurological events that do occur, the utility of IONM requires that an event be reversible.…”
Section: Discussionmentioning
confidence: 99%